WiP abstract: Optimal multi-agent path planning for fast inverse modeling in UAV-based flood sensing applications - Abdelkader, M.; Shaqura, M.; Ghommem, M.; Collier, N.; Calo, Victor; Claudel, C. (2014)
Floods are one of the most commonly occurring natural disasters, and caused more than 120,000 fatalities in the world between 1991 and 2005. Most of these casualties are caused by the lack of a reliable real-time flash flood monitoring system. Given the area to monitor, unmanned aerial vehicles (UAVs) appear as the most promising solutions for this task. © 2014 IEEE.